Prognostic Value of Her2/neu Expression in Gastrointestinal Stromal Tumors: Immunohistochemical Study. (10th February 2017) - Abd El-Aziz, Ahmed M; Ibrahim, Eman A; Abd-Elmoghny, Ashraf; El-Bassiouny, Mohammed; Laban, Zina M; Saad El-Din, Somaia A; Shohdy, Youhanna
Background: Gastrointestinal stromal tumor (GIST) is a relatively rare type of neoplasms. In Egypt, it represents 2.5% of gastrointestinal tumors and 0.3% of all malignancies. Most of the GISTs develop in the stomach. Aim: To reveal the significance of Her2/neu immunohistochemical expression in GIST and its correlation with other histopathologic parameters and tumor relapse after regular follow-up. Patients and methods: This study is a retrospective and prospective cohort. It included 32 patients with GISTs, who were resectable with no distant metastasis. Immunohistochemical staining by Her2/neu was performed after complete surgical resection of the tumors with preservation of the pseudocapsule. Results: In total, 53.1% of cases were men and 46.9% women. Tumors were classified into low-risk (25%), intermediate-risk (21.9%), and high-risk groups (53.1%). Her2/neu expression was negative in 56.3% of GISTs and positive in 43.7%. Its expression was significantly correlated with risk grade ( P = .04), tumor size ( P = .001), mitotic count ( P = .00), and increased risk of relapse ( P = .00). Furthermore, tumor relapse was significantly correlated with the tumor mitotic counts ( P = .00). Using kappa agreement test, it showed that 4 mitotic counts/50 high-power fields (HPF) was the cutoff value with which the tumor might be associated more with relapse, with 83% sensitivity, 70% specificity, and P value of .003. Conclusions: Her2/neu might be used as an independent prognostic marker for tumor recurrence after complete resection of GIST, and the cutoff value of mitotic count that might predict tumor relapse is 4/50 HPF. However, more clinical studies with greater number of cases with fluorescent in situ hybridization integration are recommended.